1971
DOI: 10.1159/000197092
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Ethanol, Dietary Lipids, and Proteins on the Rat Pancreas

Abstract: 124 male Wistar rats weighing 80–120 g were randomized into 2 groups, one receiving ad libitum 20% ethanol, the other water as drinking fluid. Each group has been divided in series of 8 to 12 rats which received 4 different diets combining different ratios of casein and fats. The experiments lasted from 2 to 21 months. Trypsinogen, amylase, lipase, protein and DNA were measured at the end of the experiment. The action of ethanol is closely related to the dietary ratio of proteins and lipids: (1) With a 17–18.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1971
1971
1992
1992

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The effect of ethanol is slight and varies according to the protein level of the diet. It is noteworthy that with diet T2, whose protein level is normal and lipid level relatively high, ethanol lowers the number of zymogen granules whereas, under the same conditions, the biochemical data [6] showed an increased enzyme content (units of amylase, lipase, chymotrypsinogen, trypsinogen per tig of DNA). At first this discrepancy could be related to an increase in the quantity of pancreatic juice pooled into the ducts: this would be enhanced by the fact that, according to Lowy el al.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of ethanol is slight and varies according to the protein level of the diet. It is noteworthy that with diet T2, whose protein level is normal and lipid level relatively high, ethanol lowers the number of zymogen granules whereas, under the same conditions, the biochemical data [6] showed an increased enzyme content (units of amylase, lipase, chymotrypsinogen, trypsinogen per tig of DNA). At first this discrepancy could be related to an increase in the quantity of pancreatic juice pooled into the ducts: this would be enhanced by the fact that, according to Lowy el al.…”
Section: Discussionmentioning
confidence: 97%
“…fats 60%). For the composition of these diets, sec table I in the first paper [6], For each diet, the rats were randomized in 2 groups: one drinking water, the other drinking ad libitum 20% ethanol. The daily intake of ethanol is given in the first paper [6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, however, increasing enzymatic contents of the pancreas were found: after 6 months 15% ethanol + normal protein diet (12), and after 2 months of 20% ethanol + lipid rich diet (8,22).…”
Section: Discussionmentioning
confidence: 83%
“…(2) In a series of studies, after alcohol consumption for variable times up to 30 months, the enzymatic contents of pancreas were generally decreased (1,21,22), in variable amounts, sometimes significantly, and sometimes not. This was observed with various diets (normal, protein deficient, lipid deficient or lipid rich) in variable degrees for the various pancreatic enzymes.…”
Section: Discussionmentioning
confidence: 99%